"Silk Road" as foreign policy discourse: The construction of Chinese, Japanese and Korean engagement strategies in Central Asia. Issue 1 (January 2018) - Dadabaev, Timur
Abstract: Through analysis of the evolution of the Japanese, Chinese and South Korean narratives of the Silk Road, this paper argues that the content and the nature of these Silk Road strategies changed with time and the international environment. Thus, this paper claims that, the notion of the Silk Road has changed from a static concept of a historical trade route into a product of social construction of a number of powerful states – strategies that are constantly shaped, imagined and re-interpreted. In this sense, the Silk Road is not a foreign policy doctrine but rather a discursive strategy of engagement that largely exists in the realm of narration. This narration is also a matter of social construction that is subject to change depending on the international environment of the country (China, Japan, Korea, etc.) that produces such narratives, context of a receiving region, the alternative narratives that compete for wider international acceptance and the country's vision of "self" and the "other" in the international context.